Levelized Cost of CO2 Captured Using Five Physical Solvents in Pre-combustion Applications. (October 2020) - Ashkanani, Husain E.; Wang, Rui; Shi, Wei; Siefert, Nicholas S.; Thompson, Robert L.; Smith, Kathryn; Steckel, Janice A.; Gamwo, Isaac K.; Hopkinson, David; Resnik, Kevin; Morsi, Badie I.
Highlights: Aspen Plus v8.8 was used to perform techno-economic analysis (TEA) of a CO2 capture process from a typical fuel gas stream in a 543-MW pre-combustion power plant. Five physical solvents (Selexol, PEGPDMS-1, NMP, [aPy][Tf2N] and [hmim][Tf2N]) and two packings, Mellapak 250Y and IMTP50, were used in the simulation. The Levelized costs of CO2 captured (LCOC) were calculated. Mellapak 250Y exhibited lower LCOC values than those when using IMTP50 for the five solvents under all conditions employed. The CO2 capture process carried out at low temperatures showed lower LCOC values than those at higher temperatures. Comparing the lowest LCOC values for the five solvents, the hydrophobic PEGPDMS-1 solvent was the most promising one. Abstract: Aspen Plus v8.8 was used to perform techno-economic analysis (TEA) of a CO2 capture process from a typical fuel gas stream in a 543-MW pre-combustion power plant using five different physical solvents (Selexol, PEGPDMS-1, NMP, [aPy][Tf2 N] and [hmim][Tf2 N]). The process included a countercurrent packed-bed absorber operating under high-pressure over a wide range of temperatures and three pressure-swing flash drums for solvent regeneration. Two packings, Mellapak 250Y and IMTP50, were used and the Levelized costs of CO2 captured (LCOC) were calculated. The simulation results indicated that using Mellapak 250Y exhibited lower LCOC values than those when using IMTP50 for the five solvents under all conditions used as it offered better mass transfer. The CO2 capture process carried out at low temperatures showed lower LCOC values than those at higher temperatures due to the increased CO2 solubility in the solvents at lower temperatures, requiring smaller absorber diameter and lower solvent circulation rates, which offset the cooling requirements. Comparing the lowest LCOC values for the five solvents, the hydrophobic PEGPDMS-1 solvent was the most promising one compared to the other four solvents, due to its lowest capital and operating costs and noncorrosive, which enabled using less expensive materials for the process equipment.